2010
DOI: 10.1158/1078-0432.ccr-09-1487
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Liver Tumor Growth and Metastasis by Adiponectin in Nude Mice through Inhibition of Tumor Angiogenesis and Downregulation of Rho Kinase/IFN-Inducible Protein 10/Matrix Metalloproteinase 9 Signaling

Abstract: Purpose: We aimed to investigate the effects of adiponectin on liver cancer growth and metastasis and explore the underlying mechanisms.Experimental Design: An orthotopic liver tumor nude mice model with distant metastatic potential was applied. Either Ad-adiponectin (1 × 10 8 ; treatment group) or Ad-luciferase (control group) was injected via portal vein after tumor implantation. Tumor growth and metastasis were monitored by Xenogen In vivo Imaging System. Hepatic stellate cell activation by α-smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 34 publications
2
91
0
Order By: Relevance
“…SIRT1, as a master regulator of cellular metabolism, might provide a crucial link between metabolic homeostasis and inhibition of cancer metastasis, by either preventing a hypoxic and/or inflammatory response downstream of the metabolic disorder, or by promoting the synthesis and release of humoral factors that have anti-metastatic properties. Indeed, several known targets of SIRT1, such as adiponectin, whose dysfunction contributes to metabolic syndrome, have been implicated in cancer metastasis (Man et al, 2010). To support this notion are the observations that calorie restriction (CR), a well-studied process known to activate SIRT1, offers some beneficial effects in combating cancer (Bonorden et al, 2009;Lee and Longo, 2011;van Ginhoven et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1, as a master regulator of cellular metabolism, might provide a crucial link between metabolic homeostasis and inhibition of cancer metastasis, by either preventing a hypoxic and/or inflammatory response downstream of the metabolic disorder, or by promoting the synthesis and release of humoral factors that have anti-metastatic properties. Indeed, several known targets of SIRT1, such as adiponectin, whose dysfunction contributes to metabolic syndrome, have been implicated in cancer metastasis (Man et al, 2010). To support this notion are the observations that calorie restriction (CR), a well-studied process known to activate SIRT1, offers some beneficial effects in combating cancer (Bonorden et al, 2009;Lee and Longo, 2011;van Ginhoven et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not include hepatitis virus infection status as a matching variable and treated anti-HCV as a confounding factor. Although in vitro and in vivo studies have indicated that adiponectin exerts antitumor effects against hepatocelluar carcinoma by inducing apoptosis or suppressing tumor angiogenesis (12,13), it is not unusual for the results of epidemiologic studies to contradict those of experimental studies. In addition, the insulin-sensitizing properties of adiponectin do not explain the connection with liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggested that elevated levels of adiponectin would be associated with a reduced risk of primary liver cancer linked with obesity, and that hyperadiponectinemia might suppress liver tumorigenesis (11). Indeed, experimental studies indicated that adiponectin treatment increased apoptosis of hepatocelluar carcinoma, the most common form of primary liver cancer, and inhibited its proliferation (12,13). However, it has been pointed out that hyperadiponectinemia reflects the progression of liver disease leading to the development of liver cancer, as the liver is the main organ of adiponectin metabolism (9,11).…”
Section: Introductionmentioning
confidence: 95%
“…It is also possible that fenofibrate differentially regulates pathological and physiological angiogenesis, as has been proposed for the effects of statins on vascularization (32). Similarly, adiponectin enhances angiogenic responses in mouse ischemic hindlimb and rabbit cornea angiogenesis assays (18,25,33), whereas adiponectin suppresses tumor angiogenesis in vivo (6,20). Of importance, it is established that activation of AMPK/eNOS signaling confers a proangiogenic phenotype in ischemic hindlimb (18,22,23,26,33).…”
Section: E563mentioning
confidence: 98%